Identification and Molecular Characterization of Foot and Mouth Disease Virus Based on VP1 Gene Fragments in Madura Cattle and Ongole Grade Cattle - Sulistyaningrum, E.; Wibawa, H.; Wibowo, M. H. (Faculty of Animal Science, IPB University, 2024)
Foot and mouth disease (FMD) is an infectious vesicular disease of cloven-hoofed animals caused by the FMD virus. It is acute, highly contagious, and has a lot of genetic diversity. The aim of this study was to confirm cases diagnosed in the field as FMD virus (FMDV) infection through identification and molecular characterization based on the amplification of the VP1 gene of FMDV to provide information about serotype, virus clustering, and additional molecular scientific data on FMDV circulating in Indonesia. The samples used in this study were Madura cattle and Ongole Grade cattle, which showed clinical signs of FMD. Twenty-six samples were collected from the vesicular fluid of blister epithelial cells (tongue, gum, and hard palate), oral, and nasal swabs. Those samples underwent a screening test using the real-time reverse transcription-polymerase chain reaction (RT-qPCR) method with a 3D gene target to detect FMDV infection. About 46.15% of samples (12/26) were detected as RT-qPCR positive for FMDV. Those positive results were then amplified by reverse transcription-polymerase chain reaction (RT-PCR) and sequenced using the Sanger sequencing technique targeting the VP1 gene fragment of the FMDV. The sequencing results were analyzed by the Molecular Evolutionary Genetics Analysis (MEGA) software X version, which includes assembly, alignment using ClustalW, amino acid prediction, genetic distance, and phylogenetic tree construction. The result showed that amino acid sequence variations were found in this gene, including at positions 96, 99, 129, 134, 138, 140, 156, 158, and 197, and no changes were found either at the critical amino acid sites at positions 144 (V), 148 (L), 154 (K), and 208 (P) or in the arginine-glycine-aspartic acid (RGD) motif at positions 145–147. Phylogenetic analysis indicated that FMD viruses detected in this study were identified as serotype “O”, topotype “Middle East South Asia (ME-SA)”, lineage “Ind-2001”, and sub-lineage “e” (O/ME-SA/Ind-2001e), which have high homology to the VP1 gene (99–100%) between the viruses studied and the viruses found at the beginning of the FMD outbreak in Indonesia in 2022.